Controlling embedment and surface chemistry of nanoclusters in metal-organic frameworks - Coupry, D.; Butson, J.; Petkov, P.; Saunders, M.; O'Donnell, K.; Kim, H.; Buckley, Craig; Addicoat, M.; Heine, T.; Szilagyi, P. (The Royal Society of Chemistry, 2016)
A combined theoretical and experimental approach demonstrates that nanocluster embedment into the pores of metal–organic frameworks (MOF) may be influenced by the chemical functionalisation of the MOF. Furthermore, this results in the surface functionalisation of the embedded nanoclusters, highlighting the potential of MOF scaffolds for the design and synthesis of novel functional materials.